Punishment, Liberalism, and Public Reason. Issue 1 (2nd January 2017) - Flanders, Chad
Abstract : The article argues for a conception of the justification of punishment that is compatible with a modern, politically liberal regime. Section I deals with what some have thought are the obvious social interests society has in punishing criminals, and tries to develop those possible interests somewhat sympathetically. Section II suggests that many of those reasons are not good ones if punishment is regarded (as it should be) from the perspective of political philosophy. Social responses to bad things happening to people cannot be grounded in controversial metaphysical views about what is good for people or what people deserve, but many reasons proffered for punishment are in fact grounded in such views. This constraint, accordingly, limits what individuals can expect in terms of a societal response to crime. Section III develops the appropriate reasons for punishment in a modern, liberal regime. Here the article relies on a—largely undefended—conception of public reason as the most plausible theory of what reasons for punishment are available to liberals. Section IV offers some closing thoughts on why people might adopt a politically liberal view about punishment as their own, personal view about how they should relate to others.